Differences In Emotional Mental Health Between Boys and Girls - Arditya, Jefry; Mercado, Myrna (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Emotional mental health that often occurs during adolescence is anxiety and academic stress. The aim of this research is to determine the differences in emotional mental health between male and female adolescents. The design of this research was cross sectional, taking the entire population as a sample with a total of 319 male adolescents and 319 female adolescents. research site for junior high school number 5, Blitar City, East Java, Indonesia. This research instrument uses the SDQ (Strengths and Difficulties Questionnaire). The results showed that the emotional mental health of male adolescents was 69% normal, borderline 12.2%, and abnormal 18.8%. Meanwhile, the emotional mental health of young women is 59.6% normal, borderline 19.4%, and 21% abnormal. The results of the Mann Whitney test obtained a p-value of 0.033 < 0.05, so it can be concluded that there are differences in the emotional mental health of female and male adolescents. The level of emotional mental health of adolescents is mostly in the normal category for both male and female students. Emotional mental health in adolescents is a phenomenon that must receive special attention from schools through Guidance and Counseling teachers and education through the School Health Unit.